Faktor Risiko Kejadian Dispepsia - Herman Herman; Sulfiyana H. Ambo Lau (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Dyspepsia is a syndrome consisting of pain or discomfort in the gut, bloating, nausea, vomiting, belching, feeling full quickly, and a full stomach. The purpose of this study was to determine the risk factors for dyspepsia, with a total of 112 cases in April 2019. This study used the Analytical Observational method with a Cross-Sectional Study approach. The research location based on the existing population was carried out in the scope of the work area of ​​the Bira Community Health Center in Makassar City with a sample size of 88 respondents from the calculation using the Slovin formula. Sampling using purposive sampling with consideration of the inclusion and exclusion criteria of population characteristics. Primary data collection uses a questionnaire with a Gutman scale and secondary data uses references related to problem needs found in the research location. Statistical results using the Chi-Square Test based on data found in the field show p-value = 0.003 ≤ 0.05 which indicates a significant relationship in knowledge behavior, p = 0.711 ≥ 0.05 which indicates no significant relationship with age, p = 0.040 ≤ 0.05, which indicates that there is a significant relationship between diet and risk factors for dyspepsia. There are two factors that are at risk of affecting the incidence of dyspepsia, namely knowledge, and irregular eating patterns